Conceptual Shifts and Contextualized Practices in Education for Glocal Interaction Issues and Implications (Intercultural Communication and Language Education,, 2018)
This book employs the realm of English Language Teaching (ELT) as a discursive point of departure to explore how individuals, groups, entities and institutions apprehend, embrace, deal with, manipulate, problematize and resist glocal flows of people, ideas, information, goods, and technology. It apprehends and attends to tensions arising from the fluidly local-global construction and negotiation of borders of identity and interaction within a diverse array of contexts and English education therein. These tensions, whether conceptual or pedagogical, may arise in and through governmental and institutional policymaking, teacher training, or curriculum and materials development, and in the learning experience both within and beyond the classroom, as teachers and students engage with course content and each other.